William & Catherine :a royal wedding - Morton, Andrew, 1953- (St. Martin's Press, 2011)
Provides an inside look at Prince William and Kate Middleton, delving into their backgrounds, their meeting as students at the University of St Andrews, the ups and downs of their relationship, their engagement, and their wedding.